SISTEM PAKAR KLASIFIKASI ANAK KAMBING KALIGESING BERBASIS WEB PADA DINAS PERTANIAN PANGAN KELAUTAN DAN PERIKANAN - Septiana Tri Andriani; Damar Eko Cahyono (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2020)
Department of Agriculture, Animal Husbandry, Fisheries and Maritime of Purworejo Regency Formed based on Purworejo Regency Local Regulation Number: 14 of 2008, to carry out local government affairs in the field of agriculture for food and Horticulture, forestry and plantations which include: Agricultural, Food Crops and Horticulture Facilities and Infrastructure, Development of Agriculture, Forestry and Plantation Businesses which are under and responsible to the Regent through the Regional Secretary. The purpose of this final project is to build an expert system of classification of web-based caligesing goats on the marine and fisheries food agriculture department. So the information presented to the community about kaligesing goats is more accurate. The method used in data collection is by interview, observation, literature study. The results of this expert system of classification of caligesing goats are two alternative choices of goat class which are presented according to the existing database rules. It is expected that this expert system can be used by the community as a starting point to determine the class of Kaligesing goats.